Life of Admiral Sir Leopold McClintock, K.C.B., D.C.L., L.L.D., F.R.S., U.P.R.G.S. - Markham, Clements R. (Clements Robert), Sir, 1830-1916. (London, J. Murray, 1909)
"Arctic fauna and flora of Greenland and the Parry Islands": p. 314-331. Mode of access: Internet.